2006
DOI: 10.1021/bm0605560
|View full text |Cite
|
Sign up to set email alerts
|

Thermoreversible Protein Hydrogel as Cell Scaffold

Abstract: A thermoreversible fibrillar hydrogel has been formed from an aqueous lysozyme solution in the presence of dithiothreitol (DTT). Its physical properties and potential as a tissue engineering scaffold have been explored. Hydrogels were prepared by dissolving 3 mM protein in a 20 mM DTT/water mixture, heating to 85 degrees C and cooling at room temperature. No gel was observed for the equivalent sample without DTT. The elastic nature of the gel formed was confirmed by rheology, and the storage modulus of our gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
147
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(159 citation statements)
references
References 30 publications
(49 reference statements)
11
147
0
1
Order By: Relevance
“…No secondary structural variation was observed after adding H 2 O 2 into the system, showing that the promotion of disulfide bond formation between the nanofibers did not cause detectable changes to the β-sheet structure (data not shown). Furthermore, complementary FTIR characterizations in D 2 O also indicated the predominance of β-sheet conformation ( Figure 6(b)), where the two peaks centering at 1621 and 1675 cm -1 are indicative of intermolecular anti-parallel β-sheet structure [36][37][38][39].…”
Section: Resultsmentioning
confidence: 95%
“…No secondary structural variation was observed after adding H 2 O 2 into the system, showing that the promotion of disulfide bond formation between the nanofibers did not cause detectable changes to the β-sheet structure (data not shown). Furthermore, complementary FTIR characterizations in D 2 O also indicated the predominance of β-sheet conformation ( Figure 6(b)), where the two peaks centering at 1621 and 1675 cm -1 are indicative of intermolecular anti-parallel β-sheet structure [36][37][38][39].…”
Section: Resultsmentioning
confidence: 95%
“…Though ENS progenitors from the ganglionic gut of children diagnosed with and without Hirschsprung's disease have been isolated, characterized and reported earlier (12), a study similar to ours using a TGP which has proven to yield an increased number of neural progenitors (13), makes this unique. Apart from this, among the various types of thermo-reversible hydrogels reported for cell culture in the literature, the TGP used in this study is novel because it is a purely synthetic hydrogel and does not contain any biological components like proteins such as Hen Egg White Lysozyme (14) or poly-saccharides such as Chitosan (15) which are used in hydrogels to improve properties like cell-adhesion (14). Further, the TGP has been proven to maintain the three-dimensional morphology (16) of different kinds of stem cells, pre-cursor cells and adult cells without alteration of their gene expression (17) for longer periods of time in contrast to other neurosphere like bodies (NLBs) were observed in culture between the 8th day and 12th day ( Figure 1) including the aganglionic sample from Patient I with Hirschsprung's disease.…”
Section: Resultsmentioning
confidence: 99%
“…Metzger et al generated NLBs from postnatal human gut mucosal tissue and after transplantation; the cells from NLBs colonized aganglionic chick and human hindgut to generate ganglia-like structures, enteric neurons and glia (1). In this study, we have examined the feasibility of culturing NLBs obtained from routine thermo-reversible hydrogels reported (14). Previous studies have suggested that from the 10th day onwards, NLBs can be observed in culture and NLBs have been grown in culture up to 28 days (2,10).…”
Section: Resultsmentioning
confidence: 99%
“…Scanning tunneling microscopy (STM) (Mikkelsen et al 2004;Kibsgaard et al 2006), transmission electron microscopy (TEM) (Kastner et al 1991;Pante et al 1997;Fu et al 2004), scanning electron microscopy (SEM) (Elias et al 2005;Yan et al 2006), atomic force microscopy (AFM) (Gould et al 1988;Marti et al 1988;Chen et al 2000), and optical tweezers (Block et al 1990;Finer et al 1994;Svoboda and Block 1994;Johnson et al 2007) have been used to image nanostructured materials, including nanomotors, with resolution in the nanometer scale. However, direct imaging or counting of biomolecules remains challenging.…”
Section: Introductionmentioning
confidence: 99%